Professional development of teachers: a post-war contexual study in the vanni districts - Kugamoorthy, S.; Lekamge, G.D.; Thanaraj, T; Zarookdeen, S.S. (University of Jaffna, 2012)
This study attempts to identify the professional development needs and aspirations of graduate teachers and assess their problems and issues to fulfil such needs and aspirations under the post-war context in three Vanni districts of Sri Lanka which have been undergoing devastating experience for the last three decades due to civil war. The main purpose of this study is to make recommendations to relevant regional and national policy makers to formulate effective strategies to develop a network to continuously upgrade professional competencies of graduate teachers. Using a mixed research method the survey design was applied to collect data from a sample of about five hundred graduate teachers and also from other stakeholders such as education officers, principals and In-service advisors mainly through questionnaires and interviews. The data were analysed using descriptive statistical techniques. The analysis revealed that the majority of the graduate teachers in the three districts did not have any professional training for a long time and whatever training they received were limited to a few components of professional development. Incidentally about fifty percent of the graduate teachers did not receive any pre-service training before their recruitment. They identified various factors such as personal problems, official bottlenecks, transport difficulties, lack of higher education institution in the districts and lack of motivation due to civil unrest etc. for their current status in professional competency. However almost all the teachers expressed their willingness to get their professional skills updated and requested for appropriate networking and structures to be established in their districts. There is a solid demand for the Open University of Sri Lanka's educational programmes. Many respondents also regretted that their working environment was not conducive to show the best of their professional performance and requested immediate inputs to improve their working environment. The study has put forward many suggestions and recommendations for the relevant authorities with regard to the professional improvement of the teachers in the Vanni districts.
Keywords: Professional development; Effective strategies; Mixed research method; Professional Training